2011
DOI: 10.1177/016146811111300302
|View full text |Cite
|
Sign up to set email alerts
|

Constancy and Change in Work Practice in Schools: The Role of Organizational Routines

Abstract: Background/ContextThough change is constant in organizations, determining how to successfully implement planned change has been a perennial challenge for both organizational scholars and practitioners. While the empirical knowledge base on planned change in schools and other organizations offers numerous insights, the inattention to activity, or the practice of leading and managing change, remains. Organizational change theory, and specifically organizational routines, offers a useful lens with which to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(14 citation statements)
references
References 64 publications
0
13
0
1
Order By: Relevance
“…Although some relationships may occur naturally, many afterschool educators intentionally cultivate them (J. N. Jones & Deutsch, 2011). Finally, program culture, defined as norms or "the way things are done around here," can be intentionally shifted by educators to encourage SEL (Hemmelgarn et al, 2006, p. 75; S. M. Jones et al, 2017b;Sherer & Spillane, 2007). For example, school-based research shows that educators can set expectations for children to use respectful language and show empathy (Bradshaw et al, 2008;Thapa et al, 2012).…”
Section: How Afterschool Educators Encourage Selmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some relationships may occur naturally, many afterschool educators intentionally cultivate them (J. N. Jones & Deutsch, 2011). Finally, program culture, defined as norms or "the way things are done around here," can be intentionally shifted by educators to encourage SEL (Hemmelgarn et al, 2006, p. 75; S. M. Jones et al, 2017b;Sherer & Spillane, 2007). For example, school-based research shows that educators can set expectations for children to use respectful language and show empathy (Bradshaw et al, 2008;Thapa et al, 2012).…”
Section: How Afterschool Educators Encourage Selmentioning
confidence: 99%
“…In addition, 12 educators described shaping a program culture and routines to support SEL. Research shows that program norms can create psychological safety and are important for child outcomes, including SE skills (S. M. Jones et al, 2017b;Pierce, 1999;Sherer & Spillane, 2007;Wanless, 2016).…”
Section: Integrating Selmentioning
confidence: 99%
“…The ostensive aspect represents standard operating procedures, taken-for-granted norms and one's subjective understanding of the routine, whereas the performative aspect represents the everyday practice of specific actions, taken by specific people, at specific times (Feldman & Pentland, 2003). Practically, examples of such organizational behavior include developing and communicating a clear vision, developing standard operating procedures, and holding teachers accountable for their own practice (Sherer & Spillane, 2011).…”
Section: Implementation Fidelity Versus Local Adaptation or Neither?mentioning
confidence: 99%
“…This is a goal at the level of the school, and therefore, it can be assumed that schools are likely to want to continue the positive changes made by individual teachers (or, at the very least, not cancel them out). Second, it is likely that schools want to change the quality of the education they provide in a way that is not dependent on individual teachers, but lasts even when certain key staff members leave the school (Sherer & Spillane, 2011). Third, previous research has extensively showed how teachers' practice and the changes they are (not) willing to make within that practice are influenced by organizational factors, including: receiving support, guidance and feedback from colleagues; a supportive school climate; and a learning culture (Thurlings, Evers, & Vermeulen, 2015).…”
Section: Implementation Fidelity Versus Local Adaptation or Neither?mentioning
confidence: 99%
“…R. Nelson, 1994). Although traditionally associated with stability, scholars have recently explored how organizational routines can be a vehicle for the diffusion of innovation (Sherer & Spillane, 2011;Spillane, 2012;Spillane, Gomez & Messler, 2009).…”
Section: Employing Theory To Guide Organizing For Improvementmentioning
confidence: 99%